Alzheimer’s disease alters the transcriptomic profile of natural killer cells at single-cell resolution - Qi, Caiyun; Liu, Fang; Zhang, Wenjun; Han, Yali; Zhang, Nan; Liu, Qiang; Li, Handong (Frontiers in Immunology, 2022)
Alzheimer’s disease (AD) is the most common dementia without an effective cure at least partially due to incomplete understanding of the disease. Inflammation has emerged as a central player in the onset and progression of AD. As innate lymphoid cells, natural killer (NK) cells orchestrate the initiation and evolution of inflammatory responses. Yet the transcriptomic features of NK cells in AD remain poorly understood. We assessed the diversity of NK cells using web-based single-cell RNA sequencing data of blood NK cells from patients with AD and control subjects and flow cytometry. We identified a contraction of NK cell compartment in AD, accompanied by a reduction of cytotoxicity. Unbiased clustering revealed four subsets of NK cells in AD, i.e.CD56bright NK cells, CD56dim effector NK cells, adaptive NK cells and a unique NK cell subset that is expanded and characterized by upregulation of CX3CR1, TBX21, MYOM2, DUSP1, ZFP36L2, and negatively correlated with cognitive function in AD patients. Pseudo-temporal analysis revealed that this unique NK cell subset was at a late stage of NK cell development and enriched with transcription factors TBX21, NFATC2 and SMAD3. Together, our study identified a distinct NK cell subset and its potential involvement in AD.